Economic development and occupational sex segregation in Puerto Rico : 1950-80 - Presser, H. B.; Kishor, S.
tbls.
pp. 53-85
Keywords: Puerto Rico; Trabajadoras; Condiciones de Trabajo; Mano de Obra; Ocupaciones; Ingresos; Analisis Demografico